Preparation and Properties of 0.9Ba(Fe0.5Ta0.5)O3-0.1BiFeO3Ceramics - Supalak Manotham (2018)
© 2015 Taylor & Francis Group, LLC. In this research, (0.9Ba(Fe 0.5 Ta 0.5 )O 3 -0.1BiFeO 3 ), (0.9BFT-0.1BFO) ceramics were fabricated via a solid state reaction technique. All ceramic samples exhibited a pure perovskite phase with cubic symmetry, while the calcined powders presented an impurity phase. Microstructures analysis by scanning electron microscopy (SEM) indicated an increase in average grain size with increasing sintering temperature. Examination of dielectric spectroscopy showed that all ceramics had high dielectric constants. An improvement in loss tangent was observed for the 1100°C ceramic. The 1200°C ceramic showed the highest dielectric constants. In addition, all ceramics exhibited non-ferroelectric property.